2021
DOI: 10.1371/journal.pmed.1003495
|View full text |Cite
|
Sign up to set email alerts
|

Safety, acceptability, and pharmacokinetics of a monoclonal antibody-based vaginal multipurpose prevention film (MB66): A Phase I randomized trial

Abstract: Background MB66 film is a multipurpose prevention technology (MPT) product with monoclonal antibodies (mAbs) against HIV-1 (VRC01-N) and HSV-1 and 2 (HSV8-N). The mAbs were produced by transient expression in Nicotiana benthamiana (N). We conducted a Phase I clinical trial to assess the safety, pharmacokinetics (PK), and ex vivo efficacy of single and repeated doses of MB66 when used intravaginally. Methods and findings The clinical trial enrolled healthy reproductive-aged, sexually abstinent women. In Segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Our team recently completed a Phase 1 clinical trial in women that tested the safety, pharmacokinetics, and ex vivo efficacy of a topically-applied vaginal film, MB66, containing IgG 1 mAbs against HIV-1 and HSV-2 that had been produced in Nicotiana. Daily vaginal application of MB66 film for seven days did not cause notable adverse events, and the concentration of active mAbs present in vaginal secretions 24 h after film application was sufficient to prevent HIV-1 and HSV-2 infection ex vivo (concentration range: 36À700 mg/ml) [12]. The HCA experiments in the present study were conducted using antibody concentrations within the range of mAbs present in vaginal secretions 24 h post-film application.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Our team recently completed a Phase 1 clinical trial in women that tested the safety, pharmacokinetics, and ex vivo efficacy of a topically-applied vaginal film, MB66, containing IgG 1 mAbs against HIV-1 and HSV-2 that had been produced in Nicotiana. Daily vaginal application of MB66 film for seven days did not cause notable adverse events, and the concentration of active mAbs present in vaginal secretions 24 h after film application was sufficient to prevent HIV-1 and HSV-2 infection ex vivo (concentration range: 36À700 mg/ml) [12]. The HCA experiments in the present study were conducted using antibody concentrations within the range of mAbs present in vaginal secretions 24 h post-film application.…”
Section: Discussionmentioning
confidence: 88%
“…The Nicotiana platform is fast and versatile, and produces a very clean antibody product free from potential contamination with mammalian pathogens. The trial demonstrated that mAbs made in Nicotiana were safe, and that effective concentrations of neutralizing antibodies could be detected in vaginal secretions for at least 24 h after film administration [12]. This study provides proof-of-concept that combinations of pathogen-specific mAbs administered intravaginally could safely protect women against a variety of STIs.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Efforts aimed primarily at developing women-controlled products against sexual HIV-1 infection have fueled a rapid growth of intravaginal drug delivery programs, mostly involving antiretroviral drugs 31 . A number of vaginal film and intravaginal ring products are in development for HIV-1 prevention, with some candidates advancing to early-stage clinical trials [32][33][34][35][36][37] . We envision that these antiretroviral agents could be coupled with sAC inhibitors, so that one product can prevent pregnancies and sexually transmitted diseases at the same time.…”
Section: Discussionmentioning
confidence: 99%